The impact of employees‘ safety training practices on the relationship between safety climate and safety performance - Mahjoub, Mohamed Salem (2013)
This research focuses on safety climate, safety performance and safety training practices. The main purpose of this research is to investigate the mediating impact of safety training practices on the relationship between safety climate and safety performance. A hundred ninety questionnaires which contain sixty five items were distributed to site workers in Mauritanian for Construction and Equipment (MCE-SA), however only a hundred and fifty four questionnaires were returned. Descriptive statistics, Pearson correlation and multiple regression analysis methods were used to analyze the collected data. The result of this study shows that the site workers in MCE-SA do have a moderate level of safety climate, safety performance and safety training practices. Besides, this study found that safety climate has a positive relationship with safety performance, and also a positive relationship between safety climate safety training practices was found. However, this study found that there is no relationship between safety training practices and safety performance. It was also found that safety training practices is mediating the relationship between safety climate and safety performance. Lastly, recommendations for MCE-SA, other industries and for future studies were presented.